PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING PADA MATERI PERSAMAAN DAN FUNGSI KUADRAT UNTUK PESERTA DIDIK KELAS IX SMP - Ayu Sangrila (Departemen Matematika, 2022)
The purpose of this reseach is toodevelop..student..worksheeti basedion iproblem basedi nlearning models on the topic Quadratic equations and function that is valid, and practical. Theeetype of this reseach is..research..and..developmentjj(R&D). The development model used is the Plomp model with threei stages, namelyopreliminaryiresearch, development or prototyping phase and assessment phase. At the development or prototyping phase , the LKPD will be revised based on a formative evaluation that concsisting of..self…evaluation,iiexpertiireviewi, ione-to-one evaluation,i iand osmalll lgroup levaluation. At the..assessment phase, only up to the practicality of LKPD. The result of this reseach are (1) The student worksheet that has developed is very valid withaaanaaaverage ivalue of 89,27%, (2) The student worksheet that has developed is very pratical withaaanaaaverage ivalue of 89,37%. Therefore, the develop students worksheet basedion iproblem ibased olearning models on.theitopic Quadratic equations and function can be rused inl mathematical learning..in schoolso.Keywords – yStudenti .Worksheet, Problem Based Learning, Quadratic Equations and Function